2015
DOI: 10.1002/adsc.201500096
|View full text |Cite
|
Sign up to set email alerts
|

DDQ‐mediated Direct C(sp3)H Cyanation of Benzyl Ethers and 1,3‐Diarylpropenes under Solvent‐ and Metal‐free Conditions

Abstract: Ad irect cyanation of benzyl ethers and 1,3-diarylpropenesw ith TMSCNw as performed under solvent-and metal-free conditions.T hiso xidative cross dehydrative coupling (CDC) reaction was promoted by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and providedr apid access to ab roadr ange of nitriles in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 67 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Compounds 1 – 1 to 1 – 32 , 3 – 1 to 3 – 30 , and 3 – 33 to 3 – 34 were prepared according to the referenced literature …”
Section: Methodsmentioning
confidence: 99%
“…Compounds 1 – 1 to 1 – 32 , 3 – 1 to 3 – 30 , and 3 – 33 to 3 – 34 were prepared according to the referenced literature …”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Huo and co-workers [73] reported the CBr4 mediated dehydrogenative coupling of isochromans with aromatic ketones, while Wo et al [74] demonstrated that the nucleophilic addition of β-keto esters to isochroman can be achieved by photoredoxneutral catalysis using a commercial dyad photosensitizer. Analogously thioethers [75] and ciano groups [76] can be introduced in the C(1) position via a CDC strategy using DTBP or DDQ as oxidant (Scheme 14, e). Amination and amidation [77] of isochroman can be obtained with FeCl3/TBHP or under metalfree conditions in the presence of DTBP (Scheme 14, f).…”
Section: Biological Properties Chemical Reactivity and Common Synthet...mentioning
confidence: 99%
“…The specific reactivity of 1,3-diphenylpropene is due to the presence of methylene group, being simultaneously in the allyl and benzyl positions. (E)-1,3-Diphenylpropene is usually obtained by treating a not easily accessible phenylacetaldehyde with a KOH alcohol solution [5,6], while the synthesis of less thermodynamically stable (Z)-isomer with an acceptable stereochemical purity is very problematic [7,8]. …”
mentioning
confidence: 99%